Reperfusion‐induced myocardial dysfunction is prevented by endogenous annexin‐A1 and its N‐terminal‐derived peptide Ac‐ANX‐A12‐26. (18th December 2012) - Qin, Chengxue; Buxton, Keith D; Pepe, Salvatore; Cao, Anh H; Venardos, Kylie; Love, Jane E; Kaye, David M; Yang, Yuan H; Morand, Eric F; Ritchie, Rebecca H
<x xml:space="preserve">Abstract</x> BACKGROUND AND PURPOSE Annexin‐A1 (ANX‐A1) is an endogenous, glucocorticoid‐regulated anti‐inflammatory protein. The N‐terminal‐derived peptide Ac‐ANX‐A12–26 preserves cardiomyocyte viability, but the impact of ANX‐A1‐peptides on cardiac contractility is unknown. We now test the hypothesis that ANX‐A1 preserves post‐ischaemic recovery of left ventricular (LV) function. EXPERIMENTAL APPROACH Ac‐ANX‐A12–26 was administered on reperfusion, to adult rat cardiomyocytes as well as hearts isolated from rats, wild‐type mice and mice deficient in endogenous ANX‐A1 (ANX‐A1–/–). Myocardial viability and recovery of LV function were determined. KEY RESULTS Ischaemia–reperfusion markedly impaired both cardiomyocyte viability and recovery of LV function by 60%. Treatment with exogenous Ac‐ANX‐A12–26 at the onset of reperfusion prevented cardiomyocyte injury and significantly improved recovery of LV function, in both intact rat and wild‐type mouse hearts. Ac‐ANX‐A12–26 cardioprotection was abolished by either formyl peptide receptor (FPR)‐nonselective or FPR1‐selective antagonists, Boc2 and cyclosporin H, but was relatively insensitive to the FPR2‐selective antagonist QuinC7. ANX‐A1‐induced cardioprotection was associated with increased phosphorylation of the cell survival kinase Akt. ANX‐A1−/− exaggerated impairment of post‐ischaemic recovery of LV function, in addition to selective LV FPR1 down‐regulation. CONCLUSIONS AND IMPLICATIONS These data represent the first evidence that ANX‐A1 affects myocardial function. Our findings suggest ANX‐A1 is an endogenous regulator of post‐ischaemic recovery of LV function. Furthermore, the ANX‐A1‐derived peptide Ac‐ANX‐A12–26 on reperfusion rescues LV function, probably via activation of FPR1. ANX‐A1‐based therapies may thus represent a novel clinical approach for the prevention and treatment of myocardial reperfusion injury.